Identification of an ethylene-responsive and cell wall-secreting β-1,3-glucanase, VvGLU1, in the early cell regrowth of grape winter buds triggered by exogenous dormancy releasers - Zhaowan Shi; Jiamin Wu; Hairuo Mo; Weiwen Xue; Zhaoqi Zhang; Xuequn Pang (BMC Biology)
Abstract Background Grape (Vitis vinifera) crops encounter significant challenges in overcoming bud endodormancy in warm winter areas worldwide. Research on the mechanisms governing bud dormancy release has focused primarily on stress regulation; however, cell wall regulation of bud meristem regrowth mechanism during the dormancy release remains obscure. Results In this study, transmission electron microscopy revealed significant changes in the grape bud cell wall following hydrogen cyanamide (HC) treatment, accompanied by an increase in β-1,3-glucanase activity. We then investigated the potential contribution of β-1,3-glucanases (GLUs) to the regulation of cell wall remodeling. Forty-eight VvGLUs distributed in clades α, β, and γ were identified and nominated based on the genome data of V. vinifera. Three γ-clade VvGLUs (VvGLU1, VvGLU16, and VvGLU32) were upregulated by dormancy-releasing stimuli, including HC, sodium azide (AZ), ethylene and hypoxia. Among these, VvGLU1 presented increased gene transcription and protein expression in response to HC and ethylene treatment. The VvGLU1 promoter positively responded to ethylene, and its activity could be activated by VvERF57. Using both immunogold labeling and GFP fusion protein analysis, we observed that VvGLU1 localized in the endoplasmic reticulum, accumulated in the vacuole, and was secreted into the cell wall during HC-triggered dormancy release. Conclusions Based on these findings, we propose that ethylene-regulated VvGLU1 plays a pivotal role in cell wall remodeling, thereby facilitating the regrowth of the bud meristem.